PELANGGARAN TERHADAP KARYA CIPTA MATERI STAND UP KOMEDI RIDWAN REMIN: Use Of Stand Up Comedy Material Without The Author's Permission Based On Law On Copyright - Cindy Rahmaputri Refra; Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2024)
Content relating to stand-up comedy is protected by copyright. The use of stand-up comedy content is basically protected by law, namely law number 28 of 2014 which regulates copyright, as shown by Ridwan Remin's use of stand-up comedy material by Vicky Prasetyo. The problem is, does the use of stand-up comedy material by Vicky Prasetyo belonging to Ridwan Remin violate Law Number 28 of 2014 concerning Copyright? and whether Vicky Prasetyo's actions using Ridwan Remin's material without permission include acts of violating copyright regulations. This type of normative research uses case and regulatory approaches, the type of research uses descriptive analysis, qualitatively analysed. The results and conclusions of the research are that stand-up comedy content is protected by copyright under Article 40 of Law Number 29 of 2014, and the use of Ridwan Remin's stand-up comedy content is unlawful under Article 44 of Law Number 28 of 2014 concerning Copyright.